Precise orbit determination for GPS satellites - Whalley, Stephen (1990)
The NAVSTAR Global Positioning System (GPS) has been under development by the US Department of Defense since 1973. Although GPS was developed for precise instantaneous position and velocity determination, it can be used for high precision relative positioning, with numerous applications for both surveyors and geodesists. The high resolution of the satellite's carrier phase has enabled relative positioning accuracies of the order of one part per million to be routinely obtained, from only one or two hours of data. These accuracies are obtained using the broadcast ephemeris, which is the orbit data that is broadcast in the satellite's radio transmission. However, the broadcast ephemeris is estimated to be in error by up to twenty five metres and this error is one of the principle limitations for precise relative positioning with GPS.